Factors Influencing Risky Sexual Behavior Among MSM and Transgender Individuals and its Relationship to Hiv/Aids Prevention: A Literature Review - Almandra, Gabriella Mariza; Sitorus, Rico Januar; Najmah, Najmah (Newinera Publisher, 2025)
HIV/AIDS remains a global public health challenge with a high prevalence among vulnerable populations, particularly men who have sex with men (MSM) and transgender individuals. These groups face various barriers, such as social stigma, discrimination, and limited access to healthcare services, which exacerbate the risk of engaging in risky sexual behavior. This study employed a literature review design. Data sources included scientific articles retrieved from Google Scholar and PubMed. Factors influencing risky sexual behavior include young age, low levels of education and knowledge, negative social environments, unstable economic conditions, and experiences of stigma and discrimination. HIV prevalence among transgender and MSM individuals in developing countries remains high (e.g., 75.7% in the Caribbean, 25–35% in Peru). Effective prevention efforts include consistent condom use, utilization of Pre-Exposure Prophylaxis (PrEP), and access to transgender-friendly healthcare services. However, major challenges remain in terms of PrEP adherence, awareness, and addressing social and structural barriers. Risky sexual behavior among MSM and transgender populations results from a complex interaction of social, economic, and structural factors. HIV/AIDS prevention requires a holistic approach, including comprehensive sexual education, inclusive and friendly healthcare services, strategies to reduce stigma and discrimination, and the promotion and facilitation of access to condoms and PrEP. Interventions should engage communities, healthcare providers, and policymakers to establish a supportive and safe system for vulnerable populations.